Integration of indigenous knowledge practices in ordinary level biology teaching and learning at Centenary High School - Boniface, J. (BUSE, 2024)
This research sought to gain an insight in the integration of indigenous knowledge practices in ordinary level biology teaching and learning activities. Data generation, analysis and interpretation was grounded in interpretivist paradigm and qualitative approach. In generating data, focus group discussions and personal interviews were used. Purposive sampling method was used to select 15 learners and 4 teachers who teach biology at ordinary level. The data generated was analysed according to emerging themes. The findings revealed that participants are familiar with IK practices and gave culture, beliefs, values, language, traditional agricultural practices, medicinal practices and local food as examples of IK. It was also revealed that IK practices were integrated into ordinary level biology learning through project-based learning and inquiry-based learning. The research study revealed that some challenges are encountered when integrating IK practices into ordinary level biology learning. From the findings it can be concluded that to some extent IK practices were being integrated into ordinary level biology learning at the selected school. Based on the findings of this study, the researcher recommends that curriculum developers should include IK in curriculum documents to promote awareness of its integration in teaching and learning
Keywords: Integration of indigenous knowledge practices; Centenary high school; Teaching biology